1993
DOI: 10.1016/1010-7940(93)90175-b
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of myocardial function *1The ultimate target of coronary revascularization

Abstract: Recovery of myocardial contraction represents an important target of coronary revascularization and the preoperative recognition of viable akinetic (hibernating) myocardium is a crucial point of the preoperative investigation of patients with chronically depressed left ventricular function. In 14 patients dobutamine infusion during echocardiography was utilized to evoke the contractile reserve retained by viable akinetic segments. Redistribution of thallium(TI)-201 after the rest injection was also used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…3 However, the few available studies with longer follow-up have shown that a delayed recovery of function may occur. 4,5,17,18 Thus, the variance in recovery of function in the studies may (in part) be related to the time course of recovery after revascularization. The differences in time course of recovery may be related to the severity of ultrastructural damage before revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the few available studies with longer follow-up have shown that a delayed recovery of function may occur. 4,5,17,18 Thus, the variance in recovery of function in the studies may (in part) be related to the time course of recovery after revascularization. The differences in time course of recovery may be related to the severity of ultrastructural damage before revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the detection of viable myocardium, the reversibility from the stress defect was considered to be equivalent to the reversibility from the rest defect. Therefore stress image acquisition was not always required for a viability assessment; the 201 Tl rest-redistribution study was considered sufficient for detection of viable myocardium (16, 17). …”
Section: Discussionmentioning
confidence: 99%
“…Third, individual viability markers may represent different phases during the progression of myocardial dysfunction and accordingly the time to full recovery after revascularization may differ. Dobutamine stress echocardiography has been reported to detect recovering dysfunctional myocardium just a few weeks after CABG (16). The dysfunctional myocardium with stress/rest reversibility mainly presented wall-motion improvement 3 months post-CABG (23).…”
Section: Discussionmentioning
confidence: 99%
“…Hibernating myocardium may recover its function with improved perfusion [7], further LV dilatation and dysfunction can be prevented, and the risk of sudden death is reduced [8]. Observational series suggest that patients with ischemic cardiomyopathy who are most likely to benefit from revascularization are those in whom a significant amount of viable myocardium (25% or more of the left ventricle) can be demonstrated preoperatively [9][10][11].…”
Section: Coronary Artery Bypass Graft Surgerymentioning
confidence: 99%